Compared analysis of physiology and transcriptomics reveals superior cold tolerance in CV-1 compared to K326 - Yang, Quanliu; Wang, Caixian; Luo, Ting; Yang, Dandan; Zhu, Jianyu; Gan, Min; Yu, Yuange (Frontiers in Plant Science, 2025)
IntroductionLow-temperature stress can cause damage to the growth and development of tobacco plants and the yield and quality of tobacco leaves.MethodsTo elucidate the physiological and molecular mechanisms underlying the differing responses of different tobacco varieties to low-temperature stress at 6 °C, transcriptomics analysis was employed to investigate the differences in physiological and gene regulatory networks between K326 and CV-1.ResultsMorphological analysis revealed that CV-1 recovered more quickly to its pre-cold stress state than K326 during the later stages of low-temperature stress, demonstrating stronger cold tolerance. Physiological and biochemical analyses showed that compared to K326, CV-1 exhibited stronger antioxidant enzyme activities (superoxide dismutase, catalase, peroxidase) and lower membrane lipid peroxidation damage, as indicated by the decreased malondialdehyde content. Differential gene expression analysis indicated that the enhanced cold tolerance of CV-1 may be attributed to stronger phenylalanine synthesis capacity, NADH synthesis, and antioxidant enzyme activities. Weighted co-expression network analysis revealed that the enhanced cold tolerance of CV-1 may be attributed to its unique SUMOylation and phosphorylation regulatory pathways of proteins such as DeSI1L, EDS1L, and EXPA2L. Compared to K326 under low-temperature stress, CV-1 also exhibits stronger photosynthetic capacity, hydrogen peroxide transport capacity, and isoflavone synthesis capacity. Additionally, CV-1 shows higher expression of the SPFH protein superfamily and heat shock protein family.DiscussionThis study revealed differences in gene regulatory networks between K326 and CV-1 in response to low-temperature stress and identified candidate genes associated with low-temperature stress, which can be utilized for genetic improvement of tobacco plants to enhance their cold tolerance.